Digitalization of North Sumatera Malay Ritual Music Using Cubase 5 Software - Wiflihani Wiflihani; Pita HD Silitonga; Herna Hirza (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The high level of need of dance artists in North Sumatra for digital audio of Malay ritual dance music while the digital material is not publicly available. This triggers researchers to conduct research on the use of this cubase music software as an alternative in the process of packaging the learning material of musical accompaniment of the Gobuk Bedagai Malay ritual dance into digital audio. The method used in this study is an experimental approach to the process of packaging the learning material of musical accompaniment of the Gobuk Bedagai Malay ritual dance into digital audio. The packaging process by recording audio and video ritual dance performances in the coastal areas of North Sumatra Malay. The results of this study indicate that the process of creating digitalization consists of recording, editing, mixing and mastering using cubase.